ECTOPIC PARATHYROID ADENOMA, A DIAGNOSTIC CHALLENGE - L, Yen Nee; M, Masni; N, Azraai Bahari; MN, Nurain; H, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Primary hyperparathyroidism is the most common cause of hypercalcemia. Approximately 85% of primary hyperparathyroidism is caused by solitary parathyroid adenomas and 5-10% of cases derived from ectopic adenomas. Ectopic parathyroid glands remain a diagnostic and operative challenge in terms of localizing the culprit gland. CASE We reported a case of primary hyperparathyroidism due to ectopic parathyroid adenoma in the thymus. This 31-yearold gentleman presented with renal calculi, confirmed primary hyperparathyroidism with hypercalcemia. However initial ultrasound and CT neck were unable to localize the parathyroid adenoma. Technetium – 99 (Tc99m) sestamibi scan repetitively showed focus in the anterior mediastinum. CT Thorax showed a nodule in the mediastinum, which coincides with the focus of increased uptake in the sestamibi scan. He subsequently underwent median sternotomy and thymectomy. Intra-operatively found left thymus with a nodule size less than 1 cm within. Histopathology confirmed an ectopic parathyroid adenoma within the left thymus. Post operatively his calcium level remains stable with minimal calcium supplement. CONCLUSION This case illustrates the challenges in localizing ectopic parathyroid adenoma, which lead to delay in the surgery